Quantitative extraction and determination of trace elements by surfactant-free liquid-liquid microextraction from aviation and motor fuels. (15th February 2022) - Spanu, Davide; Roncoroni, Gianluca; Cinosi, Amedeo; Furian, Riccardo; Siviero, Giacomo; Monticelli, Damiano
Graphical abstract: Highlights: A surfactant free microextraction method for trace element determination in fuels is presented. The effect of temperature, time, extractant volume and chemistry was quantitatively assessed. The method was validated for 12 trace elements in jet fuel and race gasoline samples. This approach is a step towards a unified method for trace element detection in fuels. Abstract: The occurrence of metals in crude oil and distillates may adversely affect oil processing, engines and turbines, plus contributing to environmental pollution, even at trace levels. Their detection is accordingly of the utmost relevance and several sample treatments have been developed for oily matrices, like sulfate ashing, microwave assisted digestion, dilution in organic solvents, and liquid–liquid (LL) extraction. The latter showed promising performances, but still suffer from several issues, like validation for a limited number of elements, lack of a clearly defined determined fraction (i.e., total concentration vs. dissolved fraction), unsatisfactory LODs, the need for matrix matched calibrations, and limited preconcentration factors. Here the development and validation of a liquid–liquid microextraction procedure without any surfactant is presented enabling the detection of the total concentration of 12 trace elements (V, Cr, Mn, Fe, Ni, Cu, Zn, Mo, Ag, Cd, Ba and Pb) in jet fuel and gasoline, and overcoming most of the mentioned drawbacks. The composition and volume of the extractant, plus the extraction time and temperature were systematically assessed by a multivariate approach, highlighting that the extractant volume is the most important factor controlling the extraction rate. Quantitative extraction of trace elements in jet fuel and race gasoline samples was achieved only under harsh conditions ( aqua regia extractant, 50 °C, one hour, with an enrichment factor equal to 20) as successfully validated by spiking experiments and the standard sulfate ashing method ASTM D5708. Quantification was performed by both ICP-MS and Total Reflection X-Ray Fluorescence (TXRF), the latter fully exploiting the high enrichment factor achieved by the proposed LL microextraction method.